A CRITICAL DISCOURSE ANALYSIS OF AUTISM SPECTRUM DISORDER NEWS IN TURKISH ONLINE MEDIA - Baytar, Birtan; Yarar, Emine (Uluslararasi Dil, Edebiyat ve Kultur Arastirmalari Dergisi, 2025)
A neurodevelopmental condition known as autism spectrum disorder (ASD) is commonly seen throughout the world. The news about this topic is included in various media forms worldwide. The mission of the media in creating perceptions about any issue is an undeniable fact. Therefore, news about individuals with ASD may have a potential effect on people's perceptions of these individuals. This study deals with the media portrayal about individuals with ASD. More specifically, this research employed critical discourse analysis in order to figure out the way individuals with ASD are portrayed in news articles in Hürriyet, which is among the most often visited news websites in Türkiye, according to Similarweb statistics. The news published in Hürriyet on April 2, 2023, Autism Awareness Day, was analyzed based on the model developed by van Dijk (2001). The analysis indicates that despite the inclusion of professional opinions in the news articles, commonly used terms linked with ASD, such as "disabled" and "treatment," only serve to enhance the existing negative and prejudiced societal perception.